Comparison of bactericidal efficiency of 7.5 MeV X-rays, gamma-rays, and 10 MeV e-beams. (August 2016) - Song, Beom-Seok; Lee, Yunjong; Moon, Byeong-Geum; Go, Seon-Min; Park, Jong-Heum; Kim, Jae-Kyung; Jung, Koo; Kim, Dong-Ho; Ryu, Sangryeol
Abstract: This study was performed to verify the feasibility of 7.5 MeV X-rays for food pasteurization through a comparison of the bactericidal efficiency with those of other sources for selected bacterial pathogens. No significant differences were observed between the overall bactericidal efficiency for beef-inoculated pathogens based on the uncertainty of the absorbed dose and variations in bacterial counts. This result supported that all three irradiation sources were effective for inactivation of food-borne bacteria and that 7.5 MeV X-rays may be used for food pasteurization. Highlights: 7.5 MeV X-rays, gamma-rays, and 10 MeV e-beams were used in this study. The bactericidal efficiency of the three types of radiation was compared. No significant differences in bactericidal efficiency were observed. 7.5 MeV X-rays may be used for food pasteurization.